CONGENITAL INSENSITIVITY TO PAIN WITH ANHYDROSIS - Muhammad shafiq Khan; Aftab Hussain; Muhammad Javed Khan (Gomal Journal of Medical Sciences, 2016)
ABSTRACT Congenital insensitivity to pain with anhydrosis (CIPA) is a rare genetic disorder characterized by inability to feel pain and temperature, and decreased or absent sweating. Familiarity to this condition is important to avoid misdiagnosing it with leprosy and other peripheral nerve diseases. An inability to feel pain may lead to repeated self-trauma (tongue, lips and finger tips) ultimately leading to self-mutilation. We report a case of CIPA who presented with a non-healing ulcer on the heel with a history of fingers being eaten by the patient himself along with multiple fractures in different bones and inability to sweat.